Visible-Light-Promoted Transition-Metal-Free Construction of 3-Perfluoroalkylated Thioflavones - Ma, Chunhua; Meng, Hui; He, Xing; Jiang, Yuqin; Yu, Bing (Frontiers in Chemistry, 2022)
A visible-light-promoted transition-metal-free perfluoroalkylation/cyclization reaction was developed with 9-mesityl-10-methylacridinium perchlorate (Acr+-Mes·ClO4−) as the photocatalyst, by which various perfluoroalkyl-substituted heterocycles including thioflavones, oxindoles, and quinoline-2,4(1H,3H)-diones were prepared at room temperature. Moreover, the potential of this sustainable method is demonstrated by the excellent in vitro anti-lymphoma and cervical carcinoma activity of the novel 3-perfluoroalkylated thioflavone 3m.